Canola grain yield and quality response to Sunn hemp cover crop, combined nano zinc and copper, and nitrogen fertiliser application under different agroecological zones - Mokgophi, Mahlare Mapula; Ayisi, Kingsley Kwabena; Kgopa, Pholosho Mmateko; Kena, Mapotso Anna (Frontiers in Plant Science, 2025)
IntroductionCanola production requires considerable nitrogen fertilisation, which negatively impacts the environment. This study evaluated the effects of Sunn hemp cover crop, nano zinc and copper, and nitrogen fertiliser on grain, oil and protein yields at Syferkuil and Ofcolaco during 2023 and 2024.MethodsCover crop was planted, slashed, and incorporated into the soil 60 days after planting, then followed by canola in a split split-plot design with 16 treatments and 3 replications. Statistical analysis was conducted using JASP software 0.19.3.ResultsResults showed increases in grain yield (17% to 43%), oil yield (21% to 68%), and protein yield (21% to 47%) with cover crop incorporation, although location-specific variances were noted. At Syferkuil, nano zinc and copper enhanced grain yield by 15% to 17% and protein yield by 16% to 27%. Nitrogen fertilisation at 120 kgN ha-1 also resulted in higher oil yields, which was comparable to 180 kgN ha-1, although this varied across seasons and locations.DiscussionOverall, cover crop, nano zinc and copper can reduce nitrogen inputs while maintaining oil yield depending on specific conditions.